ESTUDO DA APARENTE IMUNIDADE DE PUPAS DE ð˜”ð˜¶ð˜´ð˜¤ð˜¢ ð˜¥ð˜°ð˜®ð˜¦ð˜´ð˜µð˜ªð˜¤ð˜¢ L. (DIPTERA: MUSCIDAE) AO PARASITISMO DE ð˜šð˜±ð˜¢ð˜ð˜¢ð˜¯ð˜¨ð˜ªð˜¢ ð˜¦ð˜¯ð˜¥ð˜ªð˜¶ð˜´ WALKER (HYMENOPTERA: PTEROMALIDAE) - Chaves, L. E. L.; Berti Filho, E. (REVISTA DE AGRICULTURA, 2020)
ESTUDO DA APARENTE IMUNIDADE DE PUPAS DE ð˜”ð˜¶ð˜´ð˜¤ð˜¢ ð˜¥ð˜°ð˜®ð˜¦ð˜´ð˜µð˜ªð˜¤ð˜¢ L. (DIPTERA: MUSCIDAE) AO PARASITISMO DE ð˜šð˜±ð˜¢ð˜ð˜¢ð˜¯ð˜¨ð˜ªð˜¢ ð˜¦ð˜¯ð˜¥ð˜ªð˜¶ð˜´ WALKER (HYMENOPTERA: PTEROMALIDAE)